Capturing critical data elements in Juvenile Idiopathic Arthritis: initiatives to improve data capture - Meghan E. Ryan; Andrew Warmin; Bryce A. Binstadt; Colleen K. Correll; Emily Hause; Patricia Hobday; Alison Lerman; Shawn A. Mahmud; Mona M. Riskalla; Zachary Shaheen; Richard K. Vehe; Danielle R. Bullock; et al. (BMC, 2022)
Abstract Background Documentation of critical data elements is a focus of the Pediatric Rheumatology Care and Outcomes Improvement Network to aid in clinical care and research for patients with juvenile idiopathic arthritis. We aimed to increase data capture for critical data elements and hypothesized that quality improvement methodology would improve data capture. We also hypothesized that data capture for all critical data elements would be lower for virtual visits compared to in-person visits. Methods All visits for patients with JIA between 9/14/2020 and 12/31/2021 at the University of Minnesota were included. We assessed completeness of critical data element capture. Sixteen interventions with providers were conducted, including email reminders, individual discussions, group meetings, and feedback reports. We used statistical process control charts to evaluate change over time. Results Baseline included 355 patient-visits: 221 (62%) in-person and 134 (38%) virtual with critical data elements entry ranging between 50 and 60%. Post-intervention included 1,596 patient-visits: 1,350 (85%) in-person and 246 (15%) virtual, with critical data elements entry reaching 91%. All providers improved data entry during this study. In-person visits had significantly higher data capture rates than virtual visits for all 4 critical data elements. Conclusion We achieved our aim to increase critical data element documentation by focusing on provider buy-in, frequent reminders, and individualized feedback. We also found that collection of critical data elements occurred significantly less often with virtual visits than with in-person visits. Now that we improved capture of critical data elements, we can shift the focus to efforts aimed at improving outcomes for patients with juvenile arthritis.